2020
DOI: 10.1108/hff-05-2020-0298
|View full text |Cite
|
Sign up to set email alerts
|

Cross flow and heat transfer past a permeable stretching/shrinking sheet in a hybrid nanofluid

Abstract: Purpose The purpose of this paper is to study the laminar boundary layer cross flow and heat transfer on a rotational stagnation-point flow over either a stretching or shrinking porous wall submerged in hybrid nanofluids. The involved boundary layers are of stream-wise type with stretching/shrinking process along the surface. Design/methodology/approach Using appropriate similarity variables the partial differential equations are reduced to ordinary (similarity) differential equations. The reduced system of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Waini et al [16] also reported that the presence of a huge volume fraction of copper intensifies the skin friction coefficient and the local Nusselt number. Many other recent interesting investigations towards hybrid nanofluid, focusing on alumina and copper as the hybrid nanoparticles, with various configurations of parameters, have also been revealed by Yashkun et al [17], Lund et al [18,19], Aladdin et al [20], Roşca et al [21], Khashi'ie et al [22][23][24][25], Roy and Pop [26], Zainal et al [27], Anuar et al [28], Gangadhar et al [29] and Wahid et al [30].…”
Section: Introductionmentioning
confidence: 88%
“…Waini et al [16] also reported that the presence of a huge volume fraction of copper intensifies the skin friction coefficient and the local Nusselt number. Many other recent interesting investigations towards hybrid nanofluid, focusing on alumina and copper as the hybrid nanoparticles, with various configurations of parameters, have also been revealed by Yashkun et al [17], Lund et al [18,19], Aladdin et al [20], Roşca et al [21], Khashi'ie et al [22][23][24][25], Roy and Pop [26], Zainal et al [27], Anuar et al [28], Gangadhar et al [29] and Wahid et al [30].…”
Section: Introductionmentioning
confidence: 88%
“…Waini et al (2019aWaini et al ( , 2019bWaini et al ( , 2020) also reported that the presence of a huge volume fraction of copper intensifies the skin friction coefficient and the local Nusselt number. Many other recent interesting investigations toward hybrid nanofluid, focusing on alumina and copper as the hybrid nanoparticles, with various configurations of parameters, have also been revealed by Khashi'ie et al (2020aKhashi'ie et al ( , 2020bKhashi'ie et al ( , 2020cKhashi'ie et al ( , 2020d, Roy and Pop (2020), Zainal et al (2020), Ros ca et al (2020. Valuable information on nanofluids can be also found in the review papers by Huminic and Huminic (2018), Sarkar et al (2015), Akilu et al (2016), Sidik et al (2016), Sundar et al (2017), etc. Therefore, in this present study, we intended to scrutinize the mixed convection flow of a hybrid nanofluid past a vertical wedge with thermal radiation effect.…”
Section: Introductionmentioning
confidence: 91%
“…These fluids are utilized in tremendous heat transfer applications, such as heat pipes, micro-channel, mini channel heat sinks, plate heat exchangers, air conditioning systems, helical coil heat exchangers, etc. Comprehensive reviews on hybrid nanofluids were presented by Aly and Pop [8,9], Roşca et al [10,11], Waini et al [12,13], Devi and Devi [14], and in the review papers on hybrid nanofluids by Sarkarn et al [15], Akilu et al [16], Sidik et al [17], Sundar et al [18], etc.…”
Section: Introductionmentioning
confidence: 99%